The Unimagined in the English Renaissance : Poetry and the Limits of Mimesis. (Fairleigh Dickinson, 2012)
This book is about description and image in Renaissance poetry, but focuses not on descriptions that present a vivid image to the reader's mind but on those that seem to avoid doing so. Against the ancient and still active tradition that poetry is painting in words, it argues that poetry is most poetic-most distinctive from other forms-when its goals are not visual.